Cryptococcal meningitis: A delineating presentation peeping toward HIV status (Indian Journal of Case Reports, 2020)
Cryptococcal meningitis is an ominous presentation of the most common opportunistic fungal infection in patients affected by the Human immunodeficiency virus (HIV). Cryptococcus neoformans is the commonly associated species in immunocompromised patients. It is the first AIDS-defining illness in 6–10% of patients. Cryptococcosis is reported as a major opportunistic infection in India. The case of cryptococcal meningitis presented here is of a young, chronic alcoholic 28-year-old male patient with non-specific symptoms having the only significant history that he was sexually active with a woman whose husband died of unknown cause which draws attention to look for HIV status of the patient which was found to be reactive confirming it as one of the AIDS-defining illness.